INFLUENCE OF LECTURER COMPETENCE, LEARNING ENVIRONMENT, AND MOTIVATION ON STUDENT ACHIEVEMENT OF INFORMATICS BUSINESS INSTITUTE (IBI) BOGOR UNITY OF WEST JAVA PROVINCE - ISMARTAYA; ARIEF RISTIA PENGESTU; MEYDIA MEYDIA; ALFAHMI RISTIANTO; SAFUAN (CV KULTURA DIGITAL MEDIA, 2021)
Student achievement is a form of student achievement after going through various stages in the learning process and can be used to find out the extent of student success and failure in learning. Based on the observations showed that the achievements of students of the Institute of Business Informatics Unity (IBIK) Bogor West Java Province has not been optimal. This is allegedly because it is influenced by lecturer competence, learning environment, and motivation. Therefore, universities must have good lecturer competence, a learning environment and students have high motivation, so that it will be able to improve student achievement. This study aims to explain whether there is a significant influence between lecturer competence, learning environment, and motivation on student achievement of IBI Kesatuan Bogor, as well as to find out which is the most dominant and influential among the three variables dependent on lecturer competency (X1), learning environment (X2) and Motivation (X3) on student achievement (Y). This study used quantitative methods with a population of 114 students and sampled as many as 89 students where samples were determined through the Solvin Formula with a standard error of 0.1. The data collection technique used is to use questionnaires. While the data analysis technique used in this study is a multiple linear regression method with the help of SPSS 20.0 software for windows. The results showed that 1). The competence of lecturers has a positive and significant effect on the achievements of IBI Kesatuan Bogor 2). students. The level of learning environment has a positive and significant effect on the achievements of students of IBI Kesatuan Bogor. 3). Motivation has a positive and significant effect on the achievements of students of IBI Kesatuan Bogor. 4). Lecturer competency, learning environment and motivation together have a positive and significant effect on the achievements of IBI Kesatuan Bogor students.